The Effect of Fiscal Policy on the Latin American Elections During the Period 1980-2016 - Becerra Armada, Desireé; Puente, José Manuel (Revista del CLAD Reforma y Democracia, 2020)
Rulers have taken advantage of the control of fiscal instruments to improve their reputation towards the citizens in order to maintain power within their figure or in their party, which ends up generating a democratic bias that benefit their personal interests. Academic literature considers that countries with low level of development are more likely to engage in these opportunistic practices, which is consistent with the results of the region. Nevertheless, their widespread use is not enough to draw conclusions about their actual effectiveness to obtain votes. Therefore, this study has the objective to analyze the relationship between the use of fiscal instruments (public expenditure, tax revenues, and primary balance) and the electoral results of 18 Latin American countries during the period 1980-2016 using logit regressions. Findings confirm that expansions in public spending during the entire mandate and especially during the electoral period improve the probabilities of rulers and their parties to remain in power. Additionally, in these contexts citizens are willing to favor increases in tax collection to have enough resources to support the increase of expenditures and avoid fiscal balance deterioration. However, both results are only valid for the periods of established democracies, which could explain why this opportunistic behavior has strengthened during the last fifteen years. Today, economic policymakers must be aware of the perverse incentives that come into play with fiscal policy, and should seek, in favor of democracy, to toughen the checks and balances system and to increase transparency levels.
Keywords: Economic Policy; Fiscal Policy; Budget; Election; Historical Analysis; Latin America